2012
DOI: 10.1177/1066480712451245
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Foster Parent–Adolescent Relationships Through Filial Therapy

Abstract: The purpose of this article is to explore the application of filial therapy as a means of strengthening relationships between foster parents and adolescent foster children. Adolescents in foster care experience a number of placement disruptions and while a number of therapeutic interventions are implemented to assist adolescents in foster care, very few are aimed at strengthening the foster parent–foster child bond. Studies have repeatedly shown filial therapy as an effective method for strengthening parent–ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Given the results of this study, it may also be important to encourage foster parents to understand their role and provide ways for a caregiver to build the relationship with the youth in their home. Capps (2012) promoted the use of filial therapy as a means for strengthening relationships between adolescents and their foster parents. In addition, Henggeler and Sheidow (2012) highlighted several family-based interventions that have been previously evaluated that have shown a reduction in negative behaviors of youth.…”
Section: Implications For Practice Research and Policymentioning
confidence: 99%
See 2 more Smart Citations
“…Given the results of this study, it may also be important to encourage foster parents to understand their role and provide ways for a caregiver to build the relationship with the youth in their home. Capps (2012) promoted the use of filial therapy as a means for strengthening relationships between adolescents and their foster parents. In addition, Henggeler and Sheidow (2012) highlighted several family-based interventions that have been previously evaluated that have shown a reduction in negative behaviors of youth.…”
Section: Implications For Practice Research and Policymentioning
confidence: 99%
“…In addition, there was an uneven distribution of those in traditional foster care and those in kinship care. While there is an uneven distribution, the breakdown of the distribution prior to the removal of other types of out-ofhome placement mirrors that of the general foster care population (AFCARS FY 2013data, 2011-2012. Future researchers should have a matched sample to investigate for any differences.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MTFC-A, youths are placed in community homes where foster caregivers are intensively trained, supervised, and supported to provide positive adult support and mentoring, close supervision, and consistent limit setting. Although this modality has been traditionally applied to young children, this intervention, as well as play therapy, has been adapted to adolescents (Capps, 2012). Another appropriate program for adolescents is filial therapy, a therapeutic intervention that focuses on improving the parentchild relationship.…”
Section: Foster Carementioning
confidence: 99%
“…The results from MTFC-A trials in the United States have indicated its effectiveness in reducing arrest rates and deviant peer affiliations for boys and girls, placement disruption and parenting for boys, and pregnancy rates and school engagement for girls (Leve et al, 2012). Filial therapy promotes connectedness between the parent and child (Landreth, 2012), and it allows adolescents and parents to participate in self-actualization and meet adolescents within their developmental framework (Capps, 2012). Although this modality has been traditionally applied to young children, this intervention, as well as play therapy, has been adapted to adolescents (Capps, 2012).…”
Section: Foster Carementioning
confidence: 99%